Optimization of machining for the maximal productivity rate of the drilling operations - Ryspek Usubamatov; Abdusamad Abdiraimov (International Journal of Mathematics for Industry)
Machining processes focused primarily on the quality of surfaces and sizes of machined workpieces, as well as minimizing costs and tool wear. Existing publications related to maximizing the productivity of machining processes, present results that are in fact sub-optimal. The increase in machining regimes improves productivity but may reduce the quality of machined products. Mathematical optimization methods help find a balance between the benefits and drawbacks of machining processes. The tool life of cutters largely influences machining productivity and sets limits on machining speed. The normative tool life equations developed in research labs do not take into account the reliability of machine units and the specificities of technological processes. The normative machining speeds are suboptimal for manufacturing processes and may not maximize productivity. This paper presents a mathematical model for optimizing the cutting speed of a drilling machine tool to achieve its maximum productivity under realistic manufacturing conditions.